Pengaruh Inokulasi Bacillus subtilis Terhadap Dinamika Pertumbuhan Vegetatif Tanaman Jagung Manis Pada Tanah Salin Dengan Aplikasi Pupuk NPK Dosis Seragam Di Kabupaten Merauke - Anwar Anwar; Mani Yusuf; Jefri Sembiring; Nurhening Yuni Ekowati (Jurnal Agrotek Lestari, 2026)
Sweet corn (Zea mays L. var. saccharata) cultivation on saline soils is constrained by osmotic and ionic stress that limits vegetative growth. High salinity disrupts water and nutrient uptake, resulting in reduced plant height, leaf development, stem diameter, and leaf area. The use of plant growth promoting rhizobacteria (PGPR), particularly Bacillus subtilis, combined with uniform NPK fertilization is considered a sustainable approach to improve plant growth under saline conditions. This study aimed to evaluate the effect of Bacillus subtilis inoculation on the vegetative growth of sweet corn grown on saline soil in Merauke Regency. The experiment was arranged in a randomized block design with seven treatments: control (without Bacillus subtilis), Bacillus subtilis at 5, 10, 15, 20, and 25 ml per plant each combined with 10 g NPK per plant, and NPK alone at 10 g per plant. Observed variables included plant height, number of leaves, stem diameter, and leaf area. The results showed that Bacillus subtilis inoculation significantly increased all vegetative growth parameters compared with the control and NPK-only treatment. The application of 10 ml Bacillus subtilis per plant combined with 10 g NPK produced the best vegetative growth response. These findings indicate that Bacillus subtilis improves rhizosphere conditions and nutrient uptake efficiency, thereby enhancing sweet corn adaptability to saline soils. Keywords: Bacillus subtilis, sweet corn, salinity, vegetative growth, NPK fertilizer